Clinical case of a patient with the natural flow of Fallot's tetrad - Rakhima Mekenbayeva; Anar Sarsembayeva; Bahytzhan Nurkeyev; Zhazira Kursanova; Nigina Mekenbayeva; Arman Akseitov (National Scientific Medical Center, 2019)
The Fallot's tetrad is a common congenital heart disease that requires radical surgical correction. Without treatment, Fallot's tetrad quickly leads to progressive right ventricular hypertrophy due to the increased resistance caused by a narrowing of the pulmonary trunk, which leads to heart failure and dilatation of the heart cavities. The Fallot's tetrad mortality rate reaches 35% in the first year of life and 50% in the first three years of life. By the age of 40, only 5% of patients with Fallot's tetrad survive. A unique feature of this clinical case is the natural life expectancy of a patient with congenital heart disease of Fallot's tetrad: not operated, with a large defect in the perimembranous part of the interatrial septum, in the advanced stage of progressive chronic heart failure with the development of pulmonary hypertension, right dilatation and left heart atrial, tricuspids, insufficiency of the II degree, decrease in global systolic function of the left ventricle. The patient was offered surgical treatment, explained the postoperative risks, which were assessed as high. The patient refused surgery, after which it was recommended inpatient treatment aimed at correcting chronic heart failure at the place of residence.